Role of self-sufficiency, productivity and diversification on the economic sustainability of farming systems with autochthonous sheep breeds in less favoured areas in Southern Europe. (4th April 2013) - Ripoll-Bosch, R.; Joy, M.; Bernués, A.
<x content-type="archive" xml:space="preserve">Abstract</x> Traditional mixed livestock cereal- and pasture-based sheep farming systems in Europe are threatened by intensification and specialisation processes. However, the intensification process does not always yield improved economic results or efficiency. This study involved a group of farmers that raised an autochthonous sheep breed (Ojinegra de Teruel) in an unfavourable area of North-East Spain. This study aimed to typify the farms and elucidate the existing links between economic performance and certain sustainability indicators (i.e. productivity, self-sufficiency and diversification). Information was obtained through direct interviews with 30 farms (73% of the farmers belonging to the breeders association). Interviews were conducted in 2009 and involved 32 indicators regarding farm structure, management and economic performance. With a principal component analysis, three factors were obtained explaining 77.9% of the original variance. This factors were named as inputs/self-sufficiency, which included the use of on-farm feeds, the amount of variable costs per ewe and economic performance; productivity, which included lamb productivity and economic autonomy; and productive orientation, which included the degree of specialisation in production. A cluster analysis identified the following four groups of farms: high-input intensive system; low-input self-sufficient system; specialised livestock system; and diversified crops-livestock system. In conclusion, despite the large variability between and within groups, the following factors that explain the economic profitability of farms were identified: (i) high feed self-sufficiency and low variable costs enhance the economic performance (per labour unit) of the farms; (ii) animal productivity reduces subsidy dependence, but does not necessarily imply better economic performance; and (iii) diversity of production enhances farm flexibility, but is not related to economic performance.